PENGARUH LABEL HALAL DAN CITRA MEREK TERHADAP KAPUTUSAN PEMBELIAN SEMELOTO - Wardi, Putri Amalia; Auliana, Rini Adriani; Ihyani, Layali; Nirwana, Baiq Nadia; Hermanto, Agus (SOLID, 2024)
Abstract – This research aims to determine the influence of halal labels and brand image on purchasing decisions for Semeloto products. This research was conducted in Mataram City with 100 women in Mataram City who bought and used Semeloto. The data collection method used was a survey with a sampling technique using purposive sampling. The data collection technique uses a questionnaire with data collection tools using a questionnaire whose validity and reliability have been tested. The results of this research show that the halal label has a positive and significant effect on purchasing decisions for Semeloto products and brand image has a positive and significant effect on purchasing decisions for Semeloto products.Keywords: Halal Label, Brand Image, Purchase Decision